Investigating Ideological Factors in Family Language Policy - Rani Septi Sapriati; Soni Mirizon; Sary Silvhiany (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2021)
A family has a role in supporting bilingual or multilingual children. In acquiring English for instance, family language policy is likely to shape the development of children bilingualism or multilingualism. Through a qualitative study in a case study design, the language ideologies of two bi-/multilingual families in Palembang were investigated and explored. The participants of this study were the Zahra and the Najwa families who brought up their children in more than one language including English. The data were collected through ethnographic interviews with the parents, grandmother, and children. Thematic analysis was used in analyzing the data of this study. The raw data were coded and classified into categories to derive big major themes regarding ideological factors that shaped language policy. The derived themes were then interpreted descriptively. The results indicated that there were some ideological factors found that contributed to the shaping of the language policy of those two families, such as social values, economical values, political values, cultural values, parents' knowledge toward language acquisition, and bi-/multilingualism. The findings of this study suggest that families need to provide support for their children in their bilingual or multilingual journey. Furthermore, stakeholders and professionals should play a role in the choice of language used in education as well as provide considerable support and assistance for language policy in family domain